2018
DOI: 10.1111/cico.12317
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Diversity and the Rise of Artist Hotspots: Exploring the Creative Class Thesis through a Neighborhood Change Lens

Abstract: The diversity of the U.S. urban population has increased dramatically in recent decades, yet the processes through which population diversity may be driving neighborhood change remain insufficiently understood. Building on Claude Fischer's subcultural theory of urbanism and other classic sociological insights, this article makes the case that population diversity shapes the character of place and drives the spatial clustering of artists and art organizations. Contributing to recent debates on Richard Florida's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 94 publications
(221 reference statements)
0
3
0
Order By: Relevance
“…Decades earlier, Ernest Burgess (1925, p. 56) expressed a similar view, pointing to the important function that inner-city industrial districts played as spaces of “regeneration” where artists, immigrants, and political radicals, “all obsessed with the vision of a new and better world,” generated new ideas and new forms of cultural expression. More recent studies have supported these views, demonstrating the strong association between the emergence of artistic clusters and social diversity (Deener 2012; Graif 2018).…”
Section: Neo-bohemiamentioning
confidence: 90%
See 1 more Smart Citation
“…Decades earlier, Ernest Burgess (1925, p. 56) expressed a similar view, pointing to the important function that inner-city industrial districts played as spaces of “regeneration” where artists, immigrants, and political radicals, “all obsessed with the vision of a new and better world,” generated new ideas and new forms of cultural expression. More recent studies have supported these views, demonstrating the strong association between the emergence of artistic clusters and social diversity (Deener 2012; Graif 2018).…”
Section: Neo-bohemiamentioning
confidence: 90%
“…For Florida (2002, p. 15), artists and bohemians are now part of a larger “creative class” that dominates the symbolic economy as the main source of new ideas and innovation that drives economic growth. Like Brooks’s “bobos,” Florida’s creative class shares traditional bohemian values and is attracted to “communities [that] provide the stimulation, diversity and a richness of experiences that are the wellsprings of creativity” (also see Graif 2018; Moss 2017). Thus, the creative class tends to locate in places with particular types of urban amenities, including cafés, galleries, vibrant public spaces, and walkable neighborhoods, as well as places characterized by tolerant, progressive attitudes, particularly toward gays and lesbians.…”
Section: Neo-bohemiamentioning
confidence: 99%
“…For example, such areas have been found not only to have better access to medical care but also good transportation connectivity and natural amenities such as greenspace and water access (26). Arts organizations, particularly those that are larger with robust budgets, appear to locate in neighborhoods with higher population density, young singles, and many urban amenities (27)(28)(29). Research in this vein has identified young, educated, higher income, and technology savvy residents, as the "creative class, " arguing that catering to them in terms of a host of urban amenities will lead to economic growth city-wide (30)(31)(32).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature using occupation as a proxy for SES has shown that residential preferences may vary between types of occupational groups (Boterman et al, 2021). The definition of occupational groups may follow traditional approaches, such as blue-collar and white-collar workers (Oberti, 2020;Uesugi, 2021), or more recent ones, such as the "new middle class" (Hall & Barrett, 2018;Grzegorczyk, 2021) and the "creative class" (Florida & Mellander, 2018;Graif, 2018).…”
Section: Dimensions Of Residential Segregationmentioning
confidence: 99%